Pull-in-based μg-resolution accelerometer: characterization and noise analysis - Dias, R. A. (2011)
The pull-in time (tpi) of electrostatically actuated parallel-plate microstructures enables the realization of a high-sensitivity accelerometer that uses time measurement as the transduction mechanism. The key feature is the existence of a metastable region that dominates pull-in behavior, thus making pull-in time very sensitive to external accelerations. Parallel-plate MEMS structures have been designed and fabricated using a SOI micromachining process (SOIMUMPS) for the implementation of the accelerometer. This paper presents the experimental characterization of the microdevices, validating the concept and the analytical models used. The accelerometer has a measured sensitivity of 0.25 μs/μg and a bandwidth that is directly related to the pull-in time, BW = 1/2tpi ≈ 50 Hz. These specifications place this sensor between the state of the art accelerometers found both in the literature and commercially. More importantly, the resolution of the measurement method used is very high, making the mechanical–thermal noise the only factor limiting the resolution. The in-depth noise analysis to the system supports these conclusions. The total measured noise floor of 400 μg (100 μs) is mainly due to the contribution of the environmental noise, due to lack of isolation of the experimental setup from the building vibrations (estimated mechanical thermal noise of 2.8 μg/√Hz). The low requirements of the electronic readout circuit makes this an interesting approach for high-resolution accelerometers.